Respuesta :
Answer:
Part A)
An equation in point-slope form for the line having the slope m = 6 and containing the point (7,2).
[tex]y - 2 = 6(x-7)[/tex]
Part B)
An equation in point-slope form for the line having the slope m = -4 and containing the point (1, 9).
[tex]y - 9 = -4(x-1)[/tex]
Step-by-step explanation:
Part A)
Given
Slope m = 6
Point (7, 2)
To Determine
Find an equation in point-slope form for the line having the slope m = 6 and containing the point (7,2).
Using the point-slope form of the line equation
[tex]y-y_1=m\left(x-x_1\right)[/tex]
where
- m is the slope of the line
- (x₁, y₁) is the point
In our case:
- m = 6
- (x₁, y₁) = (7, 2)
substituting the values m = 6 and the point (x₁, y₁) = (7, 2) in the point-slope form of line equation
[tex]y-y_1=m\left(x-x_1\right)[/tex]
[tex]y - 2 = 6(x-7)[/tex]
Therefore, an equation in point-slope form for the line having the slope m = 6 and containing the point (7,2).
[tex]y - 2 = 6(x-7)[/tex]
Part B)
Given
Slope m = -4
Point (1, 9)
To Determine
Find an equation in point-slope form for the line having the slope m = -4 and containing the point (1, 9).
Using the point-slope form of the line equation
[tex]y-y_1=m\left(x-x_1\right)[/tex]
where
- m is the slope of the line
- (x₁, y₁) is the point
In our case:
- m = -4
- (x₁, y₁) = (1, 9)
substituting the values m = -4 and the point (x₁, y₁) = (1, 9) in the point-slope form of line equation
[tex]y-y_1=m\left(x-x_1\right)[/tex]
[tex]y - 9 = -4(x-1)[/tex]
Therefore, an equation in point-slope form for the line having the slope m = -4 and containing the point (1, 9).
[tex]y - 9 = -4(x-1)[/tex]